Implementasi Pembelajaran Berdiferensiasi Terhadap Perkembangan Kognitif Peserta Didik Sekolah Dasar - Dona Ayu Saputri; Harto Nuroso; Joko Sulianto (Departement of Mathematics Education, 2023)
The application of differentiated learning helps in knowing the cognitive development of students. Because it refers to the child's development in thinking and the ability to give reasons. The purpose of this study was to determine the existence of the application of differentiated learning to the cognitive development of elementary school students. This type of qualitative research with the literature review method. This literature comes from the results of research within the last 10 years. The conclusion from this study is that differentiated learning can support the cognitive development of students, especially in the learning success of each student.